A BIM-Based Study on the Comprehensive Benefit Analysis for Prefabricated Building Projects in China - Yingbo Ji; Siwei Chang; Yuan Qi; Yan Li; Hong Xian Li; Kai Qi (Advances in Civil Engineering)
Prefabricated construction has been widely accepted as an alternative to conventional cast-in-situ construction, given its improved performance. Great efforts have also been made to develop prefabricated construction technologies in China. However, there is a lack of an appropriate pattern for evaluating its comprehensive economic merits, and reasonable mathematical models for providing a comparative analysis of conventional cast-in-situ and prefabricated building projects have yet to be developed. Therefore, the research in this paper aims to comprehensively evaluate the economic benefits of implementing prefabricated construction techniques in order to surpass the economic barrier and promote the development of prefabricated buildings in China. The comprehensive economic evaluation is formulated in terms of resource-use efficiencies, project progress, and incentive policies. An apartment building in Shanghai is selected as a case study. Construction progress is simulated on the BIM platform when the same case study is rationally transformed from the prefabricated to the conventional cast-in-situ construction technique. The results reveal that the comprehensive economic merit can reach ¥739.6/m2 when selecting the prefabricated construction process. The economic benefit brought by shortening the construction period can be regarded as the most significant contributor. Yet, the current incentive policies only contribute 7.1% of the comprehensive economic evaluation. Overall, this research contributes an assessment framework for decision-making in the technique management of building construction. The BIM-based simulation approach can greatly help investors to identify the relevant economic factors and adopt the latest incentive policies.